Profil GC-MS dan Potensi Bioherbisida Ekstrak Metanol Daun Ketapang (Terminalia catappa L.) terhadap Gulma Maman Ungu (Cleome rutidosperma D.C.) - Mukarlina, Alia A. Gani, Elvi Rusmiyanto P. Wardoyo, (Jurnal Protobiont, 2017)
Ketapang (Terminalia catappa L.) is one of the plants that contains allelochemical compounds which can suppress the growth of surrounding plants that can be utilized as bioherbicide. This research aims to determine the bioactive compounds that have the potential of bioherbicide and the effective concentration of the methanol extract of T. catappa leaf that can inhibit seed germination and growth of purple Cleome (Cleome rutidosperma). The results showed that treatment of the methanol extract of T. catappa leaf can inhibit seed germination and growth of weed C. rutidosperma. The GC-MS spectral data showed that bioactive compounds that have the potential bioherbicide of the methanol extract of T. catappa leaf are Neophytadiene, 3, 7, 11, 15-tetramethyl-2 -hexadecen- 1 ol, 2, 6, 10, 14, 18, 22- tetracosahexaene and Lupeol. The methanol extract of Ketapang (T. catappa) leaf included pre-grown bioherbicide with a concentration of 0.1 g/ml. The research was conducted in Macrobiology Laboratory, Department of Biology, Faculty of Mathematics and Natural Sciences. Evaporation was carried out in the Laboratory of Wood Technology, Faculty of Forestry and the soil chemical content analysis was conducted in Soil Chemistry Laboratory, Faculty of Agriculture, University of Tanjungpura, Pontianak. The Method of Gas chromatography–mass spectrometry (GC-MS) was conducted at the Organic Laboratory of Chemistry Department, Faculty of Mathematics and Natural Sciences, University of Gadjah Mada from August to November 2016. The research used a Completely Randomized Design (CRD) with extract concentrations of 0; 0.1; 0.3; 0.5 and 0.7 g/ml each with three replications.